W sidłach teorii. Aleksandra Ubertowska: Holokaust. Auto (tanato) grafie. Warszawa, Instytut Badań Literackich PAN Wydawnictwo, 2014, ss. 367 - Krupa, Bartłomiej (Narracje o Zagładzie [czasopismo zamknięte], 2015)
The pitfalls of theory. Aleksandra Ubertowska: Holokaust. Auto (tanato) grafie. Warszawa, Instytut Badań Literackich PAN Wydawnictwo, 2014, ss. 367. Holokaust. Auto (tanato) grafie, the most recent book by a distinguished Polish researcher of the literature of the Shoah, Aleksandra Ubertowska, engages the themes which the author herself considers peripheral. The researcher emphasises the instability of the texts that are analysed – essays, women’s writing and the autobiographies of the historians of the Shoah. The main reservations of the reviewer have to do with the lack of a precise indication of the things which lie at the heart of the discourse of the Shoah and of why the selected texts – and these include e.g. the works by Primo Levy and Jean Améry – were considered marginal. Ubertowska also indulges in quite far‑fetched associations, and her argument stumbles along theoretical, excessively free‑ranging though erudite considerations. In a number of cases there is also a lack of certain important contexts, e.g. a reference to the French feminist historiography. The author of the review also has a different opinion concerning the evaluation of certain phenomena – of Raul Hilberg’s research method or of constructing an analogy between the Jewish condition and the homosexual condition. However, the publication which is here discussed is at its best when th eauthor speaks her own mind instead of resorting to the fashionable, alien, theoretical discourse.